The effect of the European Union on the post-dayton Bosnia and Herzegovina : A democratic consolidation example - Seyaz, Adnan (My University, 2012)
Demokrasi birçok bilim adamı tarafından çatışma sonrası toplumlara çözüm olarak önerilmektedir. Bu tez, Avrupa Birliği’nin Dayton Anlaşması sonrası Bosna-Hersek’e etkisini incelemekte ve ülkedeki demokratik konsolidasyon sürecini analiz etmeyi amaçlamaktadır. Bu bağlamda, 1992-1995 yılları arasındaki kanlı savaş sonrasında kurulan Bosna demokrasisi, oydaşmacı demokrasi sisteminin başarılı ve başarısız özelliklerine vurgu yapılarak incelenmiştir. Ülkede kurulan yeni düzeni daha iyi anlama imkânı sunmak için daha önce müzakere edilen ve başarısız olan barış planları, başarısızlık sebeplerine odaklanılarak analiz edilmiştir. Dayton Barış Anlaşması ile kurulan oydaşmacı sistemin özellikleri savaşan tarafları işbirliği yapma konusunda motive ettiği için detaylı bir şekilde verilmiştir. Uluslar arası toplumun Bosna-Hersek’teki varlığı ise eleştirel bir yöntem ile ele alındı. Avrupa Birliği’nin 2003 Selanik Zirvesi’nde kabul ettiği ‘Balkanların geleceğinin Avrupa Birliği içerisinde’ olduğunu belirten bildirisi, hem Bosna demokratikleşmesi hem de AB’nin Bosna-Hersek’in demokratik konsolidasyonuna etkisi açısından bir dönüm noktası olarak kabul edilmektedir. Bu tarihten sonra AB, Bosna’daki askeri operasyonunu (EUFOR) başlatarak ülkede barışın korunmasında daha fazla sorumluluk almıştır. 2003 yılında AB Polis Misyonu’nun ülkede konuşlandırılması ve AB Özel Temsilcisi’nin aynı yıl göreve başlaması, Avrupa Birliği’nin bu konudaki kararlılığını teyit etmiştir. Ülkedeki oydaşmacı demokrasi sistemi savaşan tarafları bir araya getirmeyi başarmış olsa da bazı kusurları da beraberinde getirmiştir. Bu kusurlar, aynı zamanda ülkenin iç içe geçmiş olan demokratikleşme ve Avrupalılaşma sürecinde de engel olarak görülmektedir. Bu yüzden, yeni sistemin artı ve eksileri demokratikleşme ve AB entegrasyon süreci merkeze alınarak analiz edilmiştir. Oydaşmacı Demokrasi, Bosna-Hersek, Avrupa Birliği, Demokratik Konsolidasyon, Demokratikleşme, Avrupa Bütünleşmesi

Democracy was indicated as a solution to post-conflict societies by many scholars. This thesis examined the effect of the European Union on the Post-Dayton Bosnia and Herzegovina (BiH) and aimed at analyzing the process of democratic consolidation in the country. In this context, Bosnian democracy established after the bloody war between 1992 and 1995 was examined with a focus on the successful and unsuccessful features of the consociational democratic system. In order to provide a better understanding of the Dayton order in BiH, previous peace plans which ended in failure were evaluated with a stress on the reasons of the failure. The features of the consociational system established with the Dayton Peace Accords were given to indicate the factors that motivated parties for cooperation. The existence of the International Community in BiH was assessed in a critical manner. The European Union’s declaration in Thessaloniki Summit (2003) that ‘The future of the Balkans is within the EU’ was taken as a turning point in terms of both Bosnian democratization and the effect of the EU on Bosnian democratic consolidation. The EU began to take over higher responsibility for the protection of the peace in BiH with the EU-led military operation (EUFOR) in 2004. The EU Police Mission deployed in 2003 and the EU Special Representative appointed in the same year confirmed the EU’s determination. The consociational democratic system in the country achieved bringing the warring parties together; however, it also contained some defects. These defects have been indicated as obstacles in democratization and Europeanization processes which went hand in hand in BiH. That is why; the efficient and inefficient sides of the new system were analyzed by focusing on the democratization and EU integration processes. Key Words:Consociational Democracy, Bosnia and Herzegovina, The European Union, Democratic Consolidation, Democratization, European Integration
Keywords: Avrupa Birliği; Uluslararası ilişkiler